A systematic review and meta-analysis of the Derivo Embolization Device: a novel surface-modified flow diverter for intracranial aneurysm treatment. (1st March 2022) - Monteiro, Andre; Burke, Samantha M; Baig, Ammad A; Khan, Slah; Cappuzzo, Justin M; Waqas, Muhammad; Dietrich, Joseph E; Levy, Elad I; Siddiqui, Adnan H
Abstract : Background: Surface-modified flow diverters (FDs) designed to reduce thrombogenicity represent the next frontier for intracranial aneurysm treatment. The Derivo Embolization Device (DED) is a novel FD with titanium oxide and titanium oxynitride finishing of the struts. We performed a systematic review of pertinent literature, aiming to evaluate the device's effectiveness and safety. Methods: A literature search of PubMed, Embase, and MEDLINE was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Five studies comprising 481 aneurysms were included. These studies were conducted in Turkey, Brazil, Germany, Poland, and Italy; two were prospective and three were retrospective. Twenty-six aneurysms (5.4%) were ruptured. The antiplatelet regimens were heterogeneous, but dual antiplatelet therapy was administered preprocedurally in all studies and maintained for 3–12 months before a switch to single antiplatelet therapy. The rate of periprocedural ischemic and hemorrhagic complications was 4.9% (95% CI 2.9% to 7%). Adjunctive coiling was used in 25.6% (95% CI 11.4% to 39.8%) of aneurysms. The complete angiographic occlusion rate was 81.4% (95% CI 71.3% to 91.5%), mortality rate was 2.1% (95% CI 0.4% to 3.9%), with follow-up ranging from 9 to 18 months. Delayed aneurysm rupture was reported in one patient. Conclusions: The DED has been increasingly used in other countries. We identified low rates of periprocedural complications and mortality and a high rate of complete occlusion.